Molecular typing of clinical and environmental Aspergillus fumigatus isolates from Iran using microsatellites - Hamid Badali; Tahereh Shokohi; Sadegh Khodavaysi; Maryam Moazeni; Masoumeh Farhadi; Mojtaba Nabili (Mazandaran University of Medical Sciences, 2021)
Background and Purpose: Because of the growing incidence of Aspergillus infection,typing methods of Aspergillus species are increasingly being used. Accordingly,studying the spread and population dynamics of strains isolating from clinical and environment, from a single host to large scale ecosystems is definitely needed. In the current study, we carried out a genetic analysis of nine microsatellite loci in isolates from different regions of Iran to compare and explore the genetic diversity between environmental and clinical A. fumigatus strains. Materials and Methods: Sixty-six clinical (n=43) and environmental (n= 23) isolates of A. fumigatus, have collected from six cities of Iran. All A. fumigatus isolates identified based on macroscopic and microscopic characters, the ability to grow at above 45°C, and confirmed using DNA sequencing of the partial b-tubulin gene.Sixty-six A. fumigatus isolates were subjected by microsatellite typing using three separate multiplex PCRs with a panel of nine short tandem repeats (STR) to evaluate the genetic relatedness. Results: The STR typing of 66 A. fumigatus isolates revealed 38 distinct genotypes distributed among environmental and clinical isolates. We identified 12 clones including 40 different isolates representing 60% of all isolates tested, which each clone included 2-7 isolates. Conclusion: The STR typing is considered as a valuable tool with excellent discriminatory power to study the molecular epidemiology and genotypic diversity of A.fumigatus isolates. These findings show that the high genetic diversity observed of Iranian A. fumigatus isolates with those outside Iran and formed a separate cluster.